Multi-storey automated over ground garage for cars – solution of parking problems in big urban areas - Czesław PYPNO (Transport Problems, 2008)
In the paper there is a preliminary project of automated garage with capacity of 600 cars per hour in both directions. These garages can meet parking needs resulting from an increasing number of cars in developing urban areas.